2015
DOI: 10.1089/jmf.2015.3441
|View full text |Cite
|
Sign up to set email alerts
|

Whey Protein Concentrate Hydrolysate Prevents Bone Loss in Ovariectomized Rats

Abstract: Milk is known as a safe food and contains easily absorbable minerals and proteins, including whey protein, which has demonstrated antiosteoporotic effects on ovariectomized rats. This study evaluated the antiosteoporotic effect of whey protein concentrate hydrolysate (WPCH) digested with fungal protease and whey protein concentrate (WPC). Two experiments were conducted to determine (1) efficacy of WPCH and WPC and (2) dose-dependent impact of WPCH in ovariectomized rats (10 weeks old). In Experiment I, ovariec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Ovariectomy in rats closely mimics the post-menopausal state in which endogenous oestrogen levels are significantly decreased and bone fragility is increased as a result of increased bone resorption (Kim et al 2015). Therefore, ovariectomized rats are widely used prior to human trials for osteoporosis treatments due to the similarity in the phenotypic changes observed during postmenopausal state (Egermann et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Ovariectomy in rats closely mimics the post-menopausal state in which endogenous oestrogen levels are significantly decreased and bone fragility is increased as a result of increased bone resorption (Kim et al 2015). Therefore, ovariectomized rats are widely used prior to human trials for osteoporosis treatments due to the similarity in the phenotypic changes observed during postmenopausal state (Egermann et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…They can improve bone metabolism, decrease osteoclast activity [18], and enhance organic substance content of the bone [19]. In addition, several recent studies have revealed the in vivo biological activity of collagen and gelatin peptides to bone health [20,21,22]. Chum salmon skin gelatin hydrolysates can enhance osteoblast proliferation and antagonize NaF-induced osteoblast apoptosis [23].…”
Section: Introductionmentioning
confidence: 99%
“…WPC is known to enhance the proliferation and differentiation of pre-osteoblastic MC3T3-E1 cells (Takada et al 1996) and to prevent bone loss in ovariectomised rats (Kim et al 2015). It produces active molecules such as epidermal growth factor, insulin-like growth factor, and fibroblast growth factor that can help stimulate the growth or differentiation of various cells, including bone cells (Kim et al 2015). Additionally, milk protein-derived peptides and casein phosphopeptides are generated during fermentation, which are considered to be the active components of FMPs that can modulate physiological functions (Kim et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…WPC is known to enhance the proliferation and differentiation of pre‐osteoblastic MC3T3‐E1 cells (Takada et al 1996) and to prevent bone loss in ovariectomised rats (Kim et al 2015). It produces active molecules such as epidermal growth factor, insulin‐like growth factor, and fibroblast growth factor that can help stimulate the growth or differentiation of various cells, including bone cells (Kim et al 2015).…”
Section: Resultsmentioning
confidence: 99%